2015
DOI: 10.4067/s0717-95022015000200022
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Alterations Induced by the Toxicity of Variable Sizes of Silver Nanoparticles

Abstract: SUMMARY: Silver nanoprticles (SNPs) are invested in medical, industrial and environmental applications. Little if any, is known about the morphometric alterations induced by the toxicity of SNPs. The aim of the present work is to find out the effect of variable size of SNPs on different morphometric parameters. Adult healthy male mice (BAL/C) were subjected to (10 nm, 20 nm, 40 nm 60 nm and 100 nm) SNPs for 35 days. Silver NPs caused non-significant decline on the average weight, significant decline in food co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…Our results reveal that 10 nm Ag NPs are toxic and can induce microanatomical, histochemical and ultrastructural hepatic alterations. These findings are online with some previous studies [44,[48][49][50][51]. In addition, several researchers reported that smaller NPs have great ratio of surface area to volume and have long circulating residue with potential toxicity that could be related to reactive surface area bioavailability and dissolution rate [25].…”
Section: Discussionsupporting
confidence: 90%
“…Our results reveal that 10 nm Ag NPs are toxic and can induce microanatomical, histochemical and ultrastructural hepatic alterations. These findings are online with some previous studies [44,[48][49][50][51]. In addition, several researchers reported that smaller NPs have great ratio of surface area to volume and have long circulating residue with potential toxicity that could be related to reactive surface area bioavailability and dissolution rate [25].…”
Section: Discussionsupporting
confidence: 90%
“…They concluded that a high dose of SNPs reduces the antioxidant capacity due to oxidative stress (Ranjbar et al., 2014). As other researchers have indicated (Almansour et al., 2017; Ranjbar et al., 2014), the results of this study showed that SNPs increased MDA level (well‐known LPO indicator) and a significant decrease in TAC levels in the group treated with SNPs compared to the control group. Therefore, SNPs induce ROS production and cause DNA damage, protein carbonisation and membrane oxidation by inhabiting reduced glutathione (GSH) (Ahmed et al., 2017).…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, SNPs increase the free oxygen, such as super oxidase, and also increase the oxidation of molecules including proteins which ultimately reduces the number of Leydig cells and decreases the production of testosterone. As other researchers found (Almansour et al., 2017; Rezaei‐Zarchi et al., 2013), there is a significant decrease in serum testosterone levels in the group treated with SNPs in comparison with the control group. This can be occurred due to the destruction of Leydig cells and abnormalities in the function and number of Sertoli cells and consequently disequilibrium of sex hormones.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…It is suspected that this could occur because the roselle leaf extract with various doses might be able to have a positive impact on reducing the liver weight of mice in treatment. According to Almansour [15], the liver weight of normal adult mice ranges from 1.2-1.6 g. The decreasing of the liver weight in P1, P2 and P3 was seen to be closer to the normal liver weight of mice. Thus, it seems that giving roselle leaf extract can improve the reduction in liver weight of mice.…”
Section: Liver Weight Of Micementioning
confidence: 82%